1999
DOI: 10.1002/(sici)1096-9861(19990628)409:2<237::aid-cne5>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor NR1 and NR2A/B subunit expression in trigeminal neurons during early postnatal development

Abstract: Trigeminal motoneurons (Mo5), mesencephalic trigeminal neurons (Me5), and supratrigeminal (Su5) and intertrigeminal (15) neurons are important constituents of the neural circuitry responsible for jaw movements observed during ingestive behaviors. In addition, in adult animals, N-methyl-D-aspartate (NMDA) receptors are a critical component of the brainstem circuitry responsible for reflex- and centrally activated jaw movements. However, little is known about the expression of this receptor in circuitry used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…We recently reported that, during postnatal development, synapses onto JC motoneurons exhibit distinct time course of synaptogenesis, changes of synaptic strength, and phenotypic switch of inhibitory transmitters, in close relationship with the temporal pattern of maturation of the orofacial motor system (Paik et al,2007,2011). Similarly, distinct developmental changes were reported for AMPA, NMDA, and metabotropic glutamate receptors in Vmes neurons (Turman et al,1999,2000,2001). However, little is known about the development of morphologically and/or functionally defined synapses on the somata of Vmes neurons (Wu et al,2001; Lazarov,2002,2007; Saito et al,2006).…”
supporting
confidence: 55%
“…We recently reported that, during postnatal development, synapses onto JC motoneurons exhibit distinct time course of synaptogenesis, changes of synaptic strength, and phenotypic switch of inhibitory transmitters, in close relationship with the temporal pattern of maturation of the orofacial motor system (Paik et al,2007,2011). Similarly, distinct developmental changes were reported for AMPA, NMDA, and metabotropic glutamate receptors in Vmes neurons (Turman et al,1999,2000,2001). However, little is known about the development of morphologically and/or functionally defined synapses on the somata of Vmes neurons (Wu et al,2001; Lazarov,2002,2007; Saito et al,2006).…”
supporting
confidence: 55%
“…However, electrophysiological studies have shown that the duration of excitatory postsynaptic potentials declines severalfold during the first 3 postnatal weeks (Hestrin,1992; Burgard and Hablitz,1993; Sanes,1993). In addition, the expression of various glutamate receptors subunits by neurons in the trigeminal motor nucleus is also temporally and spatially regulated during development (Turman et al,1999,2000,2001,2002; Ishihama et al,2005; Ishihama and Turman,2006). This is consistent with the possibility that the change in the functional properties of glutamatergic transmission to the JC motoneurons during postnatal development is mediated by a change in the kinetics and subtypes of glutamate receptors expressed by these neurons, without the need for significant change in the fraction of Glut + boutons.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of JC muscles increase during development (Ahlgren,1966; Inoue et al,1989), reflecting increased firing frequency of JC motoneurons (Chandler et al,1994; Inoue et al,1999; Hsiao et al,2002). The developmental changes in expression of various subtypes of glutamate receptors, including AMPA, NMDA, and metabotropic glutamate receptors by the postsynaptic motoneurons have been also studied in detail (Turman et al,1999,2000,2001,2002; Ishihama et al,2005; Ishihama and Turman,2006). In contrast, little information is available on the changes in the presynaptic element—the excitatory boutons onto JC motoneurons—during development.…”
mentioning
confidence: 99%
“…At present, the functional significance of these excitatory and inhibitory Vsup premotoneurons in jaw movement is unknown. Recently, it has been reported that various subtypes of glutamate receptors such as NMDA and groups I and II metabotropic glutamate receptors are expressed in the Vsup (Turman et al, 1999, 2001). We speculate that excitatory and inhibitory Vsup premotoneurons receive different types of peripheral inputs and are involved in neural circuits with different functions.…”
Section: Resultsmentioning
confidence: 99%